MUSCLE PHYSIOLOGY (MUSCLE CONTRACTION, TYPES OF MUSCLE FIBERS, FATIGUE) (International journal of artificial intelligence, 2025)
Muscle physiology plays a pivotal role in understanding how muscles contract, adapt to various conditions, and respond to fatigue. Muscle contraction, the process by which muscle fibers generate force, is fundamental to movement and is regulated by complex interactions between the nervous system and the muscular system. Additionally, muscle fibers can be classified into different types based on their structural and functional properties, influencing their role in various types of physical activity. Muscle fatigue, a temporary decline in muscle performance, occurs as a result of intense or prolonged physical activity and involves biochemical changes that affect muscle function. This article reviews the mechanisms underlying muscle contraction, the different types of muscle fibers, and the causes and effects of muscle fatigue.